Designing a Brain-Based Curriculum Model Focusing on Interaction and Motivation in the Secondary School - Ziaee Jazi, Zohreh; Vasefian, Farzaneh; Mazbouhi, Saeid (Iranian Journal of Educational Sociology, 2022)
Purpose: The purpose of the present research is to present a brain-based curriculum model focusing on interaction and motivation in the secondary school.Methodology: In order to achieve this goal, qualitative approach, field method and semi-structured in-depth interview techniques were used. The study population included prominent curriculum planning experts, researchers and faculty members and 15 people were interviewed based on the data saturation.The data collection tools included texts and semi-structured interviews, and the method of data analysis also included inductive thematic analysis (Attride-Stirling thematic networks).Findings: The results of the research showed that the curriculum design components included four dimensions: goals, content, teaching methods, and assessment methods, which affect students' interaction and motivation. Goals included indices of changing mental images, real learning environment, flexibility of brain-based curriculum, information storage during learning. Content included indices of development of brain ability, mechanism of brain function, cognitive learning, content understanding, triggering body and brain activity, teaching methods including practical learning, learning in the environment, cooperation in class activity, different learning style, getting students to take responsibility for learning, effectiveness of education, purposeful and conscious teaching, continuous information processing. Assessment method included self- assessment, understand the content easily, flexible learning, encouraging activities. The interaction included indices of sharing new experiences in learning; improving the brain ability; and discussing different topics. Stimulation of learning and motivation included the indices cognitive function of the brain, challenging and enjoyable learning.Conclusion: The results showed that the brain-based curriculum emphasizes on goals, content, teaching and assessment methods, which is designed with an emphasis on interaction and motivation.